Implementation of school remote drop-off walking programs: Results from qualitative interviews. (September 2021) - Bejarano, Carolina M.; Koester, MacKenzie N.; Steel, Chelsea; Carlson, Jordan A.
Abstract: Background: Remote drop-off programs allow children living "unwalkable" distances from school to walk partway by being dropped off by personal vehicle or bus closer to the school, supporting physical activity and health. However, little evidence exists to guide implementation of such programs. Methods: Semi-structured interviews were conducted with key informants from 7 remote drop-off programs to capture descriptive information and qualitative content ( e.g., barriers, facilitators, outcomes). Qualitative content was analyzed using inductive thematic analysis and identified themes were organized within implementation science frameworks. Results: Programs were from low and high socioeconomic areas (free/reduced price lunch range = 4%–92%) and initiated by various champions (school staff = 29%, parents = 29%, external = 42%). 29% of programs incorporated the yellow school bus, 43% involved >100 students, and 71% involved route distances ≥0.5 miles. Twenty themes were identified across 5 implementation science domains (Intervention Characteristics, Inner Setting, Outer Setting, Implementation Process, and Outcomes). Positive outcomes included physical activity, socialization, and improved focus for students; decreased traffic; and positive perceptions of the program by students, parents, and school staff/administrators. Barriers included traffic, weather, and student engagement. Facilitators included having a champion and support from school leaders and the community, conducting process improvements, and incentivizing participation. Conclusions: Remote drop-offs are feasible for supporting active school commuting but underutilized. Promising strategies for supporting uptake and implementation of such programs include communicating benefits, developing champions, engaging school and community leaders, and improving the neighborhood built environment. Highlights: Remote drop-off programs support health as part of active school travel. This study identified implementation factors specific to remote drop-off programs. Barriers are traffic, weather, and student engagement. Facilitators are program champions, community support, and process improvements. Improving uptake of remote drop-off programs may increase youth's physical activity.